Pengaruh Konsentrasi AgNO3 dan Suhu Sintesis terhadap Surface Plasmon Resonance (SPR) Nanopartikel Perak - R, Irwan; Zakir, Muhammad; Budi, Prastawa (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2016)
The research aims to synthesis of silver nanoparticles (AgNPs) via bio-reduction method using mangosteen skin extract. The growth of AgNPs was characterized by ultraviolet-visible spectroscopy (UV-Vis). Based on Surface Plasmon resonance (SPR) data, observation suggested that an increase of initial AgNO3 concentration along with temperature, had affected its surface Plasmon resonance trend. SPR absorption indicates that the concentration of AgNO3 and the synthesis temperature was instrumental in the formation of silver nanoparticles.